About the importance of vision screening by teachers in schools: A study from Tanzania. (November 2022) - Wilhelmsen, Gunvor Birkeland; Felder, Marion
Intact visual functions are necessary for children to reach their academic potential. In the absence of vision screening, children may have unnoticed vision disturbances and academic challenges may be attributed to other problems, such as learning or cognitive disabilities. Visual problems are detrimental to educational achievement if they are not recognised. This has lifelong consequences for the individual child but also for the wider society as educational and economic advances are stifled. Few teachers are aware how vision influences reading and learning. Tanzanian teachers went through a CPD-course to learn about vision sensory qualities and ocular motor functions and were trained in vision testing. Building on theory of vision qualities and viewing conditions in class, the teachers practised vision functions assessment. Under the supervision of vision scientists, pupils in standard 5 ( n  = 104) were tested with standardised methods. The data shows that there is a clear connection between the different sensory and ocular motor skills and that problems in one vision area influence other vision areas. Nearly 50% of the pupils had disturbances in one or more of the vision functions tested. In addition, the light conditions were challenging. When teachers learn about vision qualities and their impact on reading and learning, they understand why some pupils have reading problems, reduced motivation, disturbed self-esteem and problems with concentration. With these insights, more pupils can be helped to reach their potential.